Joseph de Maistre y la Constitución imposible - Del Búfalo, Erik (Foro Interno, 2009)
This paper analyzes the paradoxes of sovereignty outlined by De Maistre (1753-1821) in relation to the idea of popular representation, and its implications for the notions of State, sovereignty and authority, as conceived since the French revolution.